Creating Consensus Educational Goals for Pediatric Sepsis via Multicenter Modified Delphi. Issue 4 (17th September 2018) - Woods, Jason M.; Scott, Halden F.; Zaveri, Pavan P.
Abstract: Clinical care of pediatric sepsis depends on early recognition and basic initial steps and thus focused educational materials for providers in these early phases of care are needed. The authors sought to identify educational goals and establish a framework for those materials. The authors conducted a Delphi process to create consensus educational goals for the recognition and treatment of pediatric sepsis, focused on the needs of emergency and acute care providers. Experts in pediatric sepsis quality improvement and education were recruited. In each round the experts determined if a particular goal was appropriate for inclusion and provided edits if required. Free‐text responses and additional goals were accepted. The primary author deidentified and collated the responses and distributed an updated list of goals prior to each round. Five experts participated in the Delphi process. After three rounds the panelists unanimously agreed on 14 educational goals. These goals include three on recognition, five on early treatment, three on treatment response, and three on continued treatment. Using a Delphi process the authors established a list of educational goals for pediatric sepsis care. The experts largely agreed upon the initial set of goals and quickly came to consensus on the majority of topics. This highlights a foundation for any future educational interventions. In addition to creating content standards for pediatric sepsis education, this Delphi process represents a useful tool that may be adaptable to educational content development in other topics.